Membangun Fondasi Digital: Peran Data Governance dalam Strategi Transformasi yang Berkelanjutan - Sania Husna; Muhammad Irwan Padli Nasution (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
In the digital realm, a solid digital foundation is vital for organizations to operate efficiently, encompassing IT, internet infrastructure, data integration, and digital platforms that are interconnected for digital transformation and sustainable business operations. Sustainable transformation strategies are essential for organizations to tackle challenges and optimize goals amidst ongoing technological advancements, with data management playing a crucial role. Data governance is highlighted as a key element, serving not just to organize and secure data but also as the primary underpinning for sustainable transformation strategies. The article emphasizes the significance of data governance in promoting sustainable digital transformation by ensuring responsible and secure data management aligning with environmental, social, and economic objectives, ultimately becoming a cornerstone for successful digital evolution.